Effects of eicosapentaenoic acid on serum levels of selenoprotein P and organ‐specific insulin sensitivity in humans with dyslipidemia and type 2 diabetes. Issue 3 (9th November 2021) - Takeshita, Yumie; Teramura, Chisato; Kamoshita, Kyoko; Takayama, Hiroaki; Nakagawa, Hiromi; Enyama, Yasufumi; Ishii, Kiyo‐Aki; Tanaka, Takeo; Goto, Hisanori; Nakano, Yujiro; Osada, Sachie; Tanaka, Yoshiaki; et al.
ABSTRACT: Aim: Selenoprotein P (SeP, encoded by SELENOP in humans) is a hepatokine that causes insulin resistance in the liver and skeletal muscle. It was found that polyunsaturated fatty acid eicosapentaenoic acid (EPA) downregulates Selenop expression by inactivating SREBP‐1c. The present study aimed to examine the effect of EPA for 12 weeks on circulating SeP levels and insulin sensitivity in humans with type 2 diabetes. Methods: A total of 20 participants with dyslipidemia and type 2 diabetes were randomly assigned to an EPA (900 mg, twice daily) group and a control group. The primary endpoint was a change in serum SeP levels. Organ‐specific insulin sensitivity in the liver (HGP and %HGP), skeletal muscle (Rd), and adipose tissue (FFA and %FFA) were assessed using a hyperinsulinemic‐euglycemic clamp study with stable isotope‐labeled glucose infusion. Results: Serum SeP levels were not changed in either group at the end of the study. In the EPA group, the changes in SeP levels were positively correlated with the change in serum EPA levels ( r = 0.709, P = 0.022). Treatment with EPA significantly enhanced %FFA but not %HGP and Rd. The change in serum EPA levels was significantly positively correlated with the change in %HGP, and negatively correlated with changes in Rd. Conclusions: The change in serum EPA levels was positively correlated with serum SeP levels, hepatic insulin sensitivity, and negatively with skeletal muscle insulin sensitivity in humans with type 2 diabetes. The EPA‐induced enhancement of hepatic insulin sensitivity might be associated with a mechanism independent of serum SeP levels. Abstract : The increase in serum EPA level was significantly correlated positively with an increase in the suppression of hepatic glucose production by insulin during a clamp study. The increase in serum EPA level tended to be negatively correlated with changes in insulin‐stimulated glucose disposal.